PENGARUH DEGREE OF OPERATING LEVERAGE, DEGREE OF FINANCIAL LEVERAGE, DAN DEGREE OF COMBINED LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR KONTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febby Alviohanita Sari; Sugeng Priyanto (Jurnal Akuntansi dan Keuangan, 2019)
The purpose of this research is showed to know the effect of Degree of operating leverage, Degree of financial leverage, and Degree of combined leverage to profitability. The data used are secondary data from the annual financial statements of the construction and building sub sectors listed on the Indonesia Stock Exchange period 2013-2017. Purposive sampling is used as a sampling method and obtained 9 from 16 construction and building sub sectors companies listed on Indonesia Stock Exchange period 2013-2017. The type of this research is causality. Multiple linear regression analysis is used as a data analysis tool and tested with enter method form IBM SPSS versi 25. The result of the research shows that Degree of operating leverage, Degree of financial leverage, and Degree of combined leverage has significant effect on Profitability at the 69,3% significance level